Improvement of urban passenger transport ticketing systems by deploying intelligent transport systems - Jakubauskas, Gražvydas (Transport, 2006)
The main advantages and disadvantages of conventional and intelligent ticketing systems and possible positive outcomes when introducing intelligent transport solutions ‐ namely smart cards or e‐ticketing instead of conventional ones (paper tickets and magnetic cards) are analysed in the paper. Two ideas of creating an intelligent ticketing system in an urban public transport are scrutinized. The first is electronic ticket and related equipment, the second ‐ e‐ticket and functional areas of it. In the article analysis has also been made on practical outcomes related with introduction of smart cards and e‐ticketing. Practical tests and trials as well as a subsequent implementation of electronic tickets have proved unchallenged advantages of contactless smart cards against the contact ones. Nevertheless, a new age of modern technologies calls even for more effective solutions ‐ namely virtual‐ticketing systems that might be achieved through introduction of mobile technologies. Therefore, the main focus in the paper is made on the analysis of e‐ticket.First Published Online: 27 Oct 2010